Multi-Cell Type Glioblastoma Tumor Spheroids for Evaluating Sub-Population-Specific Drug Response - Sivakumar, Hemamylammal; Devarasetty, Mahesh; Kram, David E.; Strowd, Roy E.; Skardal, Aleksander (Frontiers in Bioengineering and Biotechnology, 2020)
Glioblastoma (GBM) is a lethal, incurable form of cancer in the brain. Even with maximally aggressive surgery and chemoradiotherapy, median survival is 14.5 months. These tumors infiltrate normal brain tissue, are surgically incurable, and universally recur. GBMs are characterized by genetic, epigenetic, and microenvironmental heterogeneity, and they evolve spontaneously over time and as a result of treatment. However, tracking such heterogeneity in real time in response to drug treatments has been impossible. Here we describe the development of an in vitro GBM tumor organoid model that is comprised of five distinct cellular subpopulations (4 GBM cell lines that represent GBM subpopulations and 1 astrocyte line), each fluorescently labeled with a different color. These multi-cell type GBM organoids are then embedded in a brain-like hyaluronic acid hydrogel for subsequent studies involving drug treatments and tracking of changes in relative numbers of each fluorescently unique subpopulation. This approach allows for the visual assessment of drug influence on individual subpopulations within GBM, and in future work can be expanded to supporting studies using patient tumor biospecimen-derived cells for personalized diagnostics.